2009
DOI: 10.1111/j.1540-8159.2009.02429.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Ablation in Patients with Therapeutic International Normalized Ratios

Abstract: Atrial fibrillation ablation in patients with therapeutic INR on the day of a procedure appears to be safe and feasible. Expensive outpatient anti-coagulation bridging may be safely avoided in this type of population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 23 publications
0
36
0
2
Order By: Relevance
“…13 A fixed-effects model of analysis was adopted in the absence of statistical heterogeneity, whereas a random-effects model was preferred in cases of substantial heterogeneity. Sensitivity analyses were conducted as follows: withdrawing 1 study at a time, withdrawing studies in which preprocedural bridging with low-molecular-weight heparin in the DW group was not required, 6,11,14 withdrawing low-quality studies, 6,8,11,14 and withdrawing the study in which an indirect comparison analysis with the Worldwide Survey population was performed. 2,7 Subgroup analyses were carried out to appraise the impact of baseline patient characteristics (age, sex, average CHADS 2 [congestive heart failure, hypertension, age Ն75 years, diabetes mellitus, prior stroke or TIA] score, type of AF, and left atrial diameter), procedural data and different intraprocedural anticoagulation strategies (ie, use of open-irrigation catheters, ablation techniques, administering unfractionated heparin bolus before or after the transseptal puncture, different heparin doses or target activated clotting times), and of intracardiac echography (ICE) monitoring on periprocedural complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A fixed-effects model of analysis was adopted in the absence of statistical heterogeneity, whereas a random-effects model was preferred in cases of substantial heterogeneity. Sensitivity analyses were conducted as follows: withdrawing 1 study at a time, withdrawing studies in which preprocedural bridging with low-molecular-weight heparin in the DW group was not required, 6,11,14 withdrawing low-quality studies, 6,8,11,14 and withdrawing the study in which an indirect comparison analysis with the Worldwide Survey population was performed. 2,7 Subgroup analyses were carried out to appraise the impact of baseline patient characteristics (age, sex, average CHADS 2 [congestive heart failure, hypertension, age Ն75 years, diabetes mellitus, prior stroke or TIA] score, type of AF, and left atrial diameter), procedural data and different intraprocedural anticoagulation strategies (ie, use of open-irrigation catheters, ablation techniques, administering unfractionated heparin bolus before or after the transseptal puncture, different heparin doses or target activated clotting times), and of intracardiac echography (ICE) monitoring on periprocedural complications.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous unfractionated heparin was administered in all patients, although with different doses and at different stages of the procedure (Table 2). ICE was used in 5 studies, 4,5,7,10,14 and irrigated ablation catheters were used in all but 2 studies. 6,10 The definition of thromboembolic complication was quite consistent among the included studies and basically was the composite of ischemic stroke and TIA.…”
Section: Qualitative Findingsmentioning
confidence: 99%
“…6,7 Multiple studies have shown that it is safe and effective to continue warfarin at therapeutic levels before, during, and after the procedure. [7][8][9][10] Although this approach seems to decrease the amount of heparin required to achieve an adequate ACT, it remains a challenge to achieve an acceptable ACT with a single bolus of unfractionated heparin (UFH). The main purpose of this study was to assess the factors that affect the amount of UFH needed to achieve a therapeutic ACT ≥300 seconds.…”
mentioning
confidence: 99%
“…Evidence that intraprocedural intracardiac echocardiography (ICE) reduces major bleeding complications when ablation is performed on therapeutic warfarin. 33,[37][38][39][40][41][42][43][44] Adapted from Santangeli et al 32 with permission of the publisher. Copyright © 2012, American Heart Association.…”
Section: Cost-effectiveness Of Ca As a First-line Therapy For Afmentioning
confidence: 99%